Design and development of a low-power motorcycle camshaft copying machine: feasibility and accuracy evaluation - Raynaldi Prima Kurnia Putra; Muhammad Iqbal Prihanto; Sudarwanto (Journal of Automotive and Mechanical Applied Technology, 2025)
This research aims to design, develop, and evaluate the feasibility and accuracy of a motorcycle camshaft copy machine as an alternative to protect the privacy of modified camshafts from copying or duplication. This research used the ADDIE development model, involving: (1) problem analysis and needs analysis, which then produced a motorcycle camshaft copy machine; (2) the design phase, resulting in a Safety Factor of 1.23 with a load of 22.046 lb force or 10 kg; (3) the development phase, including the process of cutting the frame steel, welding to make the frame, drilling to make holes in the frame steel, assembling the motorcycle camshaft copy machine components, and painting; (4) the implementation phase, consisting of a feasibility test with a result of "very feasible," suggesting that the motorcycle camshaft copy machine can be used in workshops; and (5) the evaluation phase, which resulted in good accuracy of the camshaft copy machine. The results of this study indicate that: (1) the motorcycle camshaft copy machine has dimensions of 60 cm in length, 50 cm in width, and 75 cm in height, weighs 26.5 kg, and has a power of 245 watts. (2) The motorcycle camshaft copy machine is declared "very feasible", with a value of 89.23%. (3) The motorcycle camshaft copy machine has good accuracy with an accuracy of ± 0.13 mm.